Employee innovation and creativity level at Sime Darby Auto Connexion Sdn Bhd / Mohammad Farid Azfar Fauzi - Fauzi, Mohammad Farid Azfar (Faculty of Business and Management, 2014)
As in modern day now, innovation and creativity among employee in any organization is important for the organization to achieve the goals that been set up. It can be one of the core competitive advantages for some organization than their competitors. In this research, the researcher choose to identify the employee innovation and creativity level in Sime Darby Auto Connexion Sdn. Bhd. In 3 of their subsidiary company which is Ford, Hertz and Land Rover that located in Petaling Jaya, Selangor. The Leadership, organization and employee behaviour are the factors that the researcher emphasized in this research. The other objective of this research is to find out what are the relationship those 3 factors with employee innovation and creativity level and which one between those 3 factors that most significant to employee innovation and creativity level in Sime Darby Auto Connexion Sdn. Bhd. This research has been conducted on 50 respondents from Sime Darby Auto Connexion Sdn. Bhd. employees to be sample of this research. The finding of this research indicates employee behaviour as the most factors that significant to employee innovatin and creativity level in this organization. This will help the employee in this organization more aware on the main factor of the employee innovation and creativity level and it will help them to increase their innovation and creativity level thus will help organization to achieve their goals. Future study should focus on the similar study but with different factors to any organization in any industry. By doing this, we can get a clearer picture on the employee innovation and creativity level that occurred in many organization in this modern day.